GAMBARAN KADAR TIROGLOBULIN PADA PASIEN KARSINOMA TIROID BERDIFERENSIASI POST TOTAL TIROIDEKTOMIDI RSUP DR. M. DJAMIL PADANG - Muhammad Furqan; Yulia Kurniawati; Zelly Dia Rofinda (SINERGI : Jurnal Riset Ilmiah, 2026)
Thyroid carcinoma is the most common malignancy found in the endocrine glands and accounts for 1% of all malignancies. The average incidence of thyroid carcinoma cases according to the National Cancer Institute (NCI) from 2012-2017 was 14.3 per 100,000 total population per year, with an average mortality rate of 0.5 per 100,000 population per year. In Indonesia in 2000, thyroid carcinoma ranked ninth out of the ten most common carcinomas (4.3%) and covered 90% of all endocrine carcinomas. Based on medical record data at Dr. M. Djamil Padang General Hospital, the incidence of thyroid carcinoma in 2015 was 373 people and increased in 2016 to 850 people. Based on the problems described above, and there has not been much research on Thyroglobulin levels as a prognostic factor for recurrence of thyroid carcinoma in Indonesia, especially Padang. Encourage the author to conduct research on differentiated thyroglobulin levels after total thyroidectomy at Dr. M. Djamil Padang General Hospital.